Penggunaan Pegfilgrastim Pada Mobilisasi Hematopoietic Stem Cells dan Progenitor Cells: Literatur Review - Ilham Hariaji (JURNAL IMPLEMENTA HUSADA, 2021)
AbstractIntroduction: Pegylated Filgrastim (Pegfilgrastim) is often used in supportive therapy to prevent fever due to neutropenia after chemotherapy in patients with malignancy. In addition, pegfilgrastim, which is a Granulocyte colony-stimulating factor (G-CSF), is also used to induce the production of hematopoietic stem cells/progenitor cells (HSPCs) for stem cell transplantation for various therapeutic purposes. This literature study aims to explain the pharmacokinetics and pharmacodynamics of pegfilgrastim, as well as its clinical applications, as preparation material for further experimental research.Research Methods: This study is a literature study, the literature search was carried out using Google Scholar with the keyword pegfilgrastim, and the inclusion criteria were literature in national and international journals with a timeframe from 2011 to 2021.Results: From the search results obtained 5000 kinds of literature, after selecting 19 kinds of literature that fall into the inclusion criteria.Conclusion: Pegfilgrastim can be used as an agent to mobilize hematopoietic stem cells/progenitor cells.